Dynamics of carbon dioxide gas (CO2): Effects of varying capability of plants to absorb CO2. (17th May 2018) - Devi, Sapna; Gupta, Nivedita
Abstract : Abstract: To explore the effects of variation in the capability of plants to absorb atmospheric carbon dioxide (CO2 ), a nonlinear mathematical model is proposed here. The model is developed under the presumption that capability of plants to inhale/store CO2 varies plantwise. Primarily, whole plant population is divided into two categories for the analysis. Qualitative analysis for boundedness of solutions, existence, and stability of equilibrium points, along with permanence of the model system is carried out. The model analysis reveals that increasing the growth rate of plants, whose capability to absorb atmospheric CO2 is more, depleted CO2 more rapidly as compared to other ones, and if we increase harvesting rate coefficient, the concentration of CO2 increases accordingly. Numerical simulations are performed to support and interpret the analytical results. Finally, the plant population is categorized in n ‐parts and model is generalized to better understand the dynamics of the ecosystem. Summary for Managers: Global warming is a very serious issue to be tackled in the present scenario. CO2 has contributed more than any driver to global warming and if it accumulates unabated, then its irreversible influence will continue. To reduce the increasing level of global warming, we have to mitigate atmospheric CO2 . One important element that can help to solve this problem, is the plantation of new forests. In plantation process, if we are planting only those plants which are the good sequesters of CO2, then it will not be preferable because every plant has its own importance in the ecosystem. So, for more precise results, managers should first categorize whole plant population and then do the analysis for the reduction of CO2 without disturbing the balance of the ecosystem. Managers should implement policies to extend the forestry area which consists those plants which are the good sequesters of CO2 and prevent unnecessary harvesting.